CsGSTU8, a Glutathione S-Transferase From Camellia sinensis, Is Regulated by CsWRKY48 and Plays a Positive Role in Drought Tolerance - Zhang, Yongheng; He, Jingyuan; Xiao, Yezi; Zhang, Yingao; Liu, Yingqin; Wan, Siqing; Liu, Lu; Dong, Yuan; Liu, Huan; Yu, Youben (Frontiers in Plant Science, 2021)
Glutathione S-transferases (GSTs) constitute a large family of enzymes with a wide range of cellular functions. Recently, plant GSTs have gained a great deal of attention due to their involvement in the detoxification of electrophilic xenobiotics and peroxides under adverse environmental conditions, such as salt, cold, UV-B and drought stress. A previous study reported that a GST gene (CsGSTU8) in tea plant was distinctly induced in response to drought, suggesting this gene plays a critical role in the drought stress response. In this study, by using quantitative real-time PCR (qRT-PCR) and β-glucuronidase (GUS) reporter lines, we further demonstrated that CsGSTU8 was upregulated in response to drought stress and exogenous abscisic acid (ABA) treatments. Overexpression of CsGSTU8 in Arabidopsis resulted in enhanced drought tolerance as indicated by the improved scavenging of excess amounts of reactive oxygen species (ROS) under drought conditions. Furthermore, we found that CsWRKY71 acts as a transcriptional activator and that its expression is induced in response to drought stress and ABA treatment. Electrophoretic mobility shift assays (EMSAs), dual-luciferase (LUC) assays and transient expression assays in tea plant leaves revealed that CsWRKY71 directly binds to the W-box elements in the promoter of CsGSTU8 and activates its expression. Taken together, our results provide additional knowledge of drought stress responses in tea plant.